Visualization And Pandemic Governance In Covid-19 Hit Malaysia - Por, Heong Hong (Taylor and Francis, 2022)
From the temple murals in Bagan to the church fresco in Europe, visualization has been a vehicle of managing public health since time immemorial and it has a vital place in the governance of the current pandemic too. As importantly, governance is a field of actions, practices and activities, of which visualization constitutes a significant part, carried out by state and non-state actors, health professionals and lay persons, with the aim to directly or indirectly improve the management of pandemic. In other words, the governance of covid-19 is not monopolized by state actors and health professionals. Community and civil society too play as significant a part. Meanwhile, the general public are not merely targets of governance. As indicated in many parts of the world in the current pandemic, the general public are also actors who actively participate in governing and overseeing the conduct of their counterparts. Even though pandemic visualization is a general trend globally, each country has its idiosyncrasies. Two years into the pandemic, Malaysia has gone through several waves of covid-19, with the latest one associated with the highly transmissible Omicron variant, and three rounds of nationwide lockdown since 2020. This essay is an exploratory attempt to capture and contemplate pandemic visualizing in Malaysia, while covid-19 outbreak is still unfolding. As a tool of governance, covid-19 visualization comes in various forms, including projection model, mapping, body marking, photographic representation and visual narratives. One form often prevails over the other as the pandemic evolves and new situation arises. More importantly, images of pandemic contain more than evidentiary character. This essay views pandemic images not merely as objects that reflect truths and facts, but as intermediaries that are endowed with meanings, while being deployed to communicate certain social perspectives, construct certain ideas of medicine and science, and structure the way (s) audience see reality (Cooter & Stein 2010; Engelmann 2018; Ehring 1994; Hattori 2011; Imada 2017; Jordanova 1990).